(untitled) (Mustansiria Dental Journal, 2018)
The aim of this study is to evaluate the relationship between the social and economic condition of the studied pupils with the health of oral and dental condition and the manifestations inside the oral cavity of those tested pupils reflected this relation. A sample of 184 pupils was collected form different middle schools with ages ranging between 12-18 years. This sample consists of 84 males and 100 females. The pupils were divided into 3 groups: Group A: pupils with missing fathers and low income level. Group B: pupils with their fathers and mothers work and of high income level. Group C: pupils with their mothers being house keepers and of middle income level. Information related to those groups of pupils were collected and statistically analyzed to obtain the relationships between the socio-economic status of the studied cases of pupils and the following variations: dental caries, teeth extraction, gingivitis, visits to the dentist and asking oral and dental services and psychological and general health status. The obtained results showed that, gingivitis, loss of teeth and dental caries will increase when the socio-economic status decreased and the opposite of that was correct. Which means those pathological conditions decreased when the socioeconomic level increased. Visits to dentists and asking for dental care depending on the dental education and the economic level of the pupils, again psychological and general health status also depend on the socio-economic levels, so according to this study many good psychological and health status were found in high income pupils.